Teaching curiosity in public affairs programs. Issue 3 (October 2019) - Hatcher, William
Through practicing curiosity by asking questions in the hopes of seeking answers, public administrators may practice empathy, build knowledge about how the world works, and in doing so, dispel ignorance in public agencies. By valuing curiosity, or dispelling ignorance about how the world works, public administrators may help create bureaucracies that are effective, democratic, and trustworthy. Thus, curiosity is a concept that can help public administrators improve the delivery of public services and better serve their communities. However, public affairs curriculum rarely addresses the topic. This article discusses the importance of curiosity in public administration, examines how public affairs programs can teach the concept, and concludes with advice on incorporating the exercises teaching curiosity in the public administration classroom.